VARIASI SISTEM PEMBAYARAN TERHADAP CASH FLOW (STUDI KASUS : PEMBANGUNAN LABORATORIUM TERPADU AKN BLITAR) - Safitri, Aida Ayu; Wiryasuta, I Ketut Hendra; Sandi, Enes Ariyanto (Universitas PGRI Semarang, 2024)
Construction projects are a form of long-term investment that requires large capital. One important aspect in construction projects is the payment system. Therefore, it is necessary to vary the payment system on the cash flow of construction projects to determine the effect of the payment variation system on the safest cash flow for the contractor. In this research, the case study used for the calculation of payment system variations on cash flow is the AKN Putra Sang Fajar Blitar integrated laboratory construction project. The payment system used is the progress term payment system. The method used to obtain these results is done by varying the down payment and work progress. There are 6 variations (V) used, namely V1 down payment (0%) work progress 20%, V2 down payment (0%) work progress 25%, V3 down payment 10% work progress 10%, V4 down payment 10% work progress 25%, V5 down payment 20% work progress 20%, V6 down payment 20% work progress 25%. From the results that have been obtained, the highest peak overdraft is in V2 amounting to -Rp5,365,573,659.76 and the lowest is in V3 amounting to -Rp2,864,421,825.56. Meanwhile, the final overdraft value is the same in each variation, which is Rp824,863,740.58. Therefore, the safest variation is V3 with the lowest peak overdraft. The effect of the variation of the payment system that has been known is that the greater the down payment in each variation, the lower the peak overdraft, as well as the smaller the work progress term, the lower the peak overdraft.